Transformasi aktivisme digital menuju aktivisme riil: Kajian atas garuda biru dan unjuk rasa 22 Agustus 2024 - Puspitasari, Maria (Journal of National Paradigm-Based Resilience Strategy, 2024)
Introduction: Digital activism is one of the faces of democracy, especially as a reflection of participation. Social media flooded with 'emergency warning' Garuda Biru Pictures on a navy-blue background after Parliament/House rejects Court Decision on August 21, 2024. It reflected democracy that was in turmoil and transitioning to real social activism, namely a demonstration at the Parliament Digital activism is one of the faces of democracy, especially as a reflection of participation. Social media flooded with 'emergency warning' Garuda Biru Pictures on a navy-blue background after Parliament/House rejects Court Decision on August 21, 2024. It reflected democracy that was in turmoil and transitioning to real social activism, namely a demonstration at the House the next day. In the context of democracy, this reflects awareness and resistance of the planned the Constitutional Court's (MK) legal ruling. This study aims to reveal the content of messages on social media about how netizens interpret democracy. Second is how the interpretation turns into demonstration activism. Methods: A qualitative approach is used to describe the two main objectives of the study by exploring them through text observations on several X Twitter accounts for the period August 21-24, 2024, supported by interviews with two informants who are experts in the field of democracy and digital activism as a way of triangulating data and methods. Finding: The results of the study show that digital activism is a form of active participation in interpreting democracy in daily life. Social media showed as the effective channel for expressing meaning and disappointment regarding democratic practices. Second, digital activism can transform into real activism when there are several prerequisites, first there is a disillusionment towards the weakening of democracy, Cumulative disillusionment becomes the driving force of real activism. And social media becomes a channel to mobilize netizens to move to uphold democracy in overseeing. And there is a sequential historical moment that harmed the nation. Conclusion: The conclusion is democracy interpreted as freedom of expression including carrying out effective mobilization for real activism demonstrations and has an impact on efforts to save democracy by cancelling the DPR's plan to withdraw the Constitutional Court's decision. The change of a digital activism into a real-tangible activism occurs when there is a disillusionment and a historical moment that makes many people aware that the nation is being harmed.